Neural Network Algorithm for Budget Expenditure Prediction in LPP RRI Gorontalo - Rubiyanto Maku (Journal La Multiapp, 2022)
In this Data Mining research, the researcher uses the Neural Network Algorithm to predict budget expenditures at LPP RRI Gorontalo, the goal is to find out how much cash spending at LPP RRI Gorontalo is on average in each month, so it will make it easier for the Treasurer to control cash disbursements in each month. month. Using 412 Expenditure Records Data from 2013 to 2021, the lowest RMSE value is at Hiden Layer 11, Training Cyle 400, Learning Rate 0.1 and Momentum 0.1 with RMSE 0.142. Prediction results look better because they are closer to Real Data, so Neural Networks can be used to predicting spending at LPP RRI Gorontalo.